2016
DOI: 10.7567/jjap.55.04ep06
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical properties of Co-doped and undoped MoS2

Abstract: Co-doped and undoped layered MoS 2 crystals were grown by the chemical vapor transport method using iodine as the transport agent. Both reflectance and piezoreflectance measurements reveal two exciton transitions of the direct band edge around 1.86 and 2.06 eV for undoped MoS 2 and 1.84 and 2.03 eV for Co-doped MoS 2 . Hall effect measurements show that the Co-doped MoS 2 sample has a lower carrier concentration and mobility than the undoped sample. These differences between undoped and Co-doped MoS 2 were att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…[5] The semiconducting 2H-MoS 2 phase supports both n-and p-type doping induced by chemical and physical means. [7][8][9][10][11] Intercalation, electronic, optical, and thermal excitations as well as mechanical strain and layer orientation have been reported. [3,[12][13][14][15][16] Sliding the sulfur atoms of one of the S-planes in the S-Mo-S layers by 1.82 Å leads to A-B-C stacking within the monolayer, where the sulfur atoms occupy the centers of the hexagons of the 2H phase, which results in the metallic 1T-MoS 2 phase.…”
mentioning
confidence: 99%
“…[5] The semiconducting 2H-MoS 2 phase supports both n-and p-type doping induced by chemical and physical means. [7][8][9][10][11] Intercalation, electronic, optical, and thermal excitations as well as mechanical strain and layer orientation have been reported. [3,[12][13][14][15][16] Sliding the sulfur atoms of one of the S-planes in the S-Mo-S layers by 1.82 Å leads to A-B-C stacking within the monolayer, where the sulfur atoms occupy the centers of the hexagons of the 2H phase, which results in the metallic 1T-MoS 2 phase.…”
mentioning
confidence: 99%
“…It is observed that I ac /I dc of Ag contact on 2H-MoTe 2 decreases faster than that of 1T-MoTe 2 interlayer electrode contact as frequency increase. The behaviour of frequency dependence PC can be described by the relation [40]:…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the I ac / I dc of Nb-doped crystal decreased faster than that of the undoped one as the frequency increased. The behavior of the frequency-dependent photocurrent can be described by the relation [43] Iac/Idc=k1×tanh(14fτ1)+k2×tanh(14fτ2) where K 1 and K 2 are the amplitude coefficients. τ 1 and τ 2 are the carrier time constants of long and short time decay processes.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the slower time response in Nb-doped crystal might be due to the influence of trap states induced by niobium impurity doping. The trap states could deteriorate the carriers’ transfer speed in the doped crystal [43]. The slower response speed that arises from trap states could also correlate with the enhanced photoresponsivity in PC measurement.…”
Section: Resultsmentioning
confidence: 99%